Examining the Impact of Religion on Civilization: Insights from Ibn Khaldun and Arnold Toynbee's Theories - Zhilwan Tahir; Abdulwahed Jalal Nuri (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
This paper examines the impact of religion on civilization through the perspectives of two prominent scholars, Ibn Khaldun and Arnold Toynbee. The paper provides an overview of Toynbee's theory of comparative civilizations, highlighting his emphasis on the comparability of diverse societies and his rejection of the notion of inherent superiority or inferiority among civilizations. The paper also explores Ibn Khaldun's cyclical theory of the rise and fall of civilizations, which emphasizes the role of religion in shaping the fortunes of societies. This study utilizes a comparative methodology to analyze the viewpoints of Ibn Khaldun and Arnold Toynbee on the impact of religion on civilization. The work explores the perspectives of individuals on social unity, governing systems, and the development of culture. It utilizes knowledge from their writings and historical circumstances to clarify the complex connection between religion and human communities. The paper investigates the impact of religious beliefs on the rise and fall of civilizations, drawing on insights from both Toynbee and Ibn Khaldun. It examines how religion has influenced the development of civilizations, including its role in shaping cultural values, political structures, and economic systems. The paper also explores how religion has contributed to the decline of civilizations, including through religious conflicts and the erosion of social cohesion. Overall, the paper provides a comparative analysis of the role of religion in civilization and society, drawing on the insights of two influential scholars. It highlights the importance of understanding the complex interplay between religion and civilization, and how religious beliefs have shaped the fortunes of societies throughout history.